Relationship between parental stress and adaptation to the virtual educational environment in contexts of technological limitations in the Milagro canton during the covid-19 pandemic - Acosta Barreno, Kevin; Escobar Cevallos, Jiomaira; Chiqui Vera, Javier Andres; Alchundia Mendoza, Maria Noemi; Landires Romero, Estefanía Margarita (Arandu UTIC, 2025)
The present study aimed to analyze parental stress levels and their relationship with the virtual educational environment during a period of forced technological adaptation..